EFEKTIVITAS BERBAGAI BIOAKTIVATOR TERHADAP PEMBENTUKAN KOMPOS DARI LIMBAH SAYUR DAN DAUN - Darmawati Darmawati (UIR Press, 2015)
This research aims to determine the effectiveness of various bio-activators on the composting of vegetable and leave waste. This research was carried out from April to November 2014. The type of research is an experiment by using a Comletely random, consisting of 4 treatments and 3 replications. Research procedure consisted of four stages, namely preparation of tools and materials, the implementation phase of composting, observation of the composting process, and the completion stage. The observed parameters were the texture, length of composting, C/N ratio of compost, temperature, humidity, and pH. Data were analyzed quantitatively using the C/N ratio and the length of time the composting and analysis of variance (ANOVA) and also DMRt test at significant level of 5%, while qualitative analysis was used for the compost texture, temperature, humidity, and pH. The results showed the effectiveness of bio-activator EM4, Acticomp, and Orgadec hade an effect on the composting of vegetable waste and leaves. Acticomp bio-activator was the best bio-activator to produce compost from vegetable waste and leaves.